Diagnóstico espacial dos geradores de resíduos de serviços de saúde: estudo de caso o meio urbano de Santa Maria, RS - Lunardi, Márcio André (2013)
According to IBGE (2000), 2300 tons per day are generated in Brazil, and of these only 14% of the waste properly treat municipal health services. Therefore, this study aimed to georeferenced establishments that generate the waste of health services, using the techniques of GIS to conduct spatial analysis of the generators in the city of Santa Maria. The specific objectives guiding those responsible for the generation of special waste to follow the rules confirmed the frequency of collections and checked the amount generated in the sampled establishments. Served also for planning with solutions in the management of the RSS and the RSS produced by quantifying the health units in the municipality. As this is a study on RSS, used for this purpose the data from interviews of PNSB held between 1998 to 2000, and research in 2008, started in October last year, both by the IBGE and the report of ANVISA 2006 for development of an instrument used in research establishments. The results verified the concentration of private activities in the city center, and space units of the municipal health districts of the city. As the frequency of collection was found to be weekly and fortnightly as the most made at the findings. To address and improve the services of collection, the adoption of agreements, or consortia, even in partnerships to ensure obtaining the most advantageous to the health of the enterprise and the service provider. To address and improve the services of collection, the adoption of agreements, or consortia, even in partnerships to ensure best value to get the company to health and the service provider.